2011
DOI: 10.1097/pep.0b013e318218efc3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight-Bearing in Abduction and Extension on Hip Stability in Children With Cerebral Palsy

Abstract: : Straddled weight-bearing, 1 hour per day, may reduce the MP after adductor-iliopsoas-tenotomies or prevent an MP increase and preserve muscle length in children with cerebral palsy who did not need surgery. Larger studies are needed to confirm the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 21 publications
2
39
0
6
Order By: Relevance
“…The results of this research support the findings of Gibson et al, 28 Martinsson and Himmelmann, 31 Salem et al, 18 and Paleg et al, 32 which show that muscle flexibility can be maintained through the use of a sustained stretching program. According to a recent systematic review by Paleg et al 32 on recommendations for pediatric standing programs, the use of standing devices seems to have positive effects on lower-extremity ROM, hip biomechanics, and spasticity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of this research support the findings of Gibson et al, 28 Martinsson and Himmelmann, 31 Salem et al, 18 and Paleg et al, 32 which show that muscle flexibility can be maintained through the use of a sustained stretching program. According to a recent systematic review by Paleg et al 32 on recommendations for pediatric standing programs, the use of standing devices seems to have positive effects on lower-extremity ROM, hip biomechanics, and spasticity.…”
Section: Discussionsupporting
confidence: 91%
“…30,31 Other authors have provided support for the use of prolonged stretch through the use of a night-time hip abduction positioning system. 36 According to the study by Martinsson and Himmelmann,31 weight-bearing with 60 • of total hip abduction and 0 • of hip extension for at least 1 hour per day reduced hip migration percentage and preserved ROM. However, we think that the use of the standing program twice a day for at least 45 minutes is better than once a day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Martinsson and Himmelmann (2011) also found that weight bearing with maximal achievable abduction and zero degrees of hip extension for at least one hour per day decreased the risk of subluxation of the hip for children with cerebral palsy. However, they pointed out that larger studies are needed to validate the evidence.…”
Section: Introductionmentioning
confidence: 94%